Analysis Of Nursing Care In Post Appendictomy Patients With The Application Of Effleurage Techniques: Analisis Asuhan Keperawatan Pada Pasien Nyeri Post Appendiktomi Dengan Penerapan Teknik Effleurage - Umi Marfungatun Mudrikah; Fajar Tri Waluyanti (Journal of Health and Cardiovascular Nursing, 2021)
Appendicitis is one of the most common surgical conditions that occur in children and adults. The incidence of appendicitis is the phenomenon that needs to be addressed immediately. One of the management of appendix is appendectomy. The main problem that arises in the patients post appendectomy is acute pain due to surgical injuries. Post-operative pain management in child patients is required the important role of nurses in conducting assessment and management of postoperative pain. The purpose of this paper is to analyze the implementation of nursing care This article aims to analyze nursing care in a patient 11-years- old boy through with pain post appendectomy with the application of effleurage technique. This articles using case study methods. The results of the application of effleurage techniques performed on the client with post appendectomy can increase the sense of comfort and reduce the pain felt by the client. This scientific work is expected to increase knowledge and become one of the evidence developed for healthcare providers regarding the application of effleurage techniques in child patients with pain post appendectomy.